An Analysis of the Motivation in Learning English as a Foreign Language of Senior High School Students - Garini, Selza Azzahra; Pratolo, Bambang Widi (Universitas Pendidikan Indonesia, 2024)
Motivation is an element that affects a student's ability to learn. There are two different kinds of motivation: integrative and instrumental. Instrumental motivation moves learners to learn a language because of positive attitudes toward the target language, culture, community, way of life, literature, etc. Integrative motivation drives individuals to learn a language for practical reasons. This study aimed to determine the motivation for learning English as a foreign language among 12th-grade senior high school students and the factors that influence the students' motivation to learn English. The type of research used was a mixed method sequential explanatory model by conducting quantitative research first, followed by qualitative data collection. To collect the quantitative data, the researcher used questionnaires. Meanwhile, to manage the qualitative data, the researcher conducts semi-structured interviews. The result of the study shows that it was found that 12th-grade high school students have both integrative and instrumental motivation. Then, four factors influence the student's motivation, namely: the teacher, the method of teaching, which refers to the way that students are taught, the Atmosphere in class, and success in learning.